Efektivitas Media Kartun terhadap Hasil Belajar Siswa pada Pembelajaran Tematik Kelas II - Imroatul Mufidah; Sri Hartatik; Nafiah Nafiah; Pance Mariati (FKIP, Universitas Palangka Raya, 2024)
Increasing educational qualifications is necessary for good knowledge, being able to convey and having an attitude of exemplary students, students of skills acquired holistically can be useful in the world of education. The role of the teacher is to make the most of learning materials and media. Learning media is used to make students interested in participating in learning and it is hoped that learning can be carried out effectively. The research aims to find out how effective cartoon media is on student learning outcomes in class II thematic learning at SD Mabadiul Ulum Surabaya using the One Group Pretset- Posttest method. In this study the aim was to find out student learning outcomes after applying cartoon media. This research was carried out on May 15, 2023. Data collection techniques used tests in the form of pretest and posttest. The results of this study indicate that there are differences in student learning outcomes before and after the application of cartoon media with an average increase of 78,667 which can be said that cartoon media is effective for use in class II thematic learning at SD Mabadiul Ulum Surabaya. Because the value is more than 0.76%.